A Survey of Open Source Installer Production Tools - Priyadharshini T; Sumathi V.P (International Journal of Computer Sciences and Engineering, 2014)
The Open source installer production tools are widely used for building software installer application. This survey paper deals with the most commonly occurring java based open source installer production tools in the software market and classified the tools according to the file packaging and distribution mechanism. This survey is mainly focused on open source installer production tools, which provides the framework for generating automated unattended installer. The automated installer is more generic installer for all types and versions of operating system and also provides the unique and clean way of distributing the software application during silent unattended installation. In the Introduction the reader is informed about the advantages of the Open source tools, furthermore discussed about types of installation, Open source Licenses, Java based installer production tools. At the end conclusion is drawn and outline some questions for future research.